The Making of a Competent Oocyte - A Review of Oocyte Development and Its Regulation - Hammed A. Tukur; Riyadh S. Aljumaah; Ayman Abdel-Aziz Swelum; Abdullah N. Alowaimer; Islam M. Saadeldin (The Korean Society of Animal Reproduction and Biotechnology, 2020)
Assisted reproductive technologies (ART) merely depend on improving the oocyte maturation and their developmental competence to produce good quality embryos. Oocyte maturation passes through long and complex molecular steps starts from the early embryonic life and ends with sperm fertilization. Oocyte developmental competence can be attained by improving the nuclear and cytoplasmic mechanisms together with some epigenetic maturation. In this review, we highlight the cornerstones of oocyte maturation on both nuclear and cytoplasmic levels. Interfering or supporting these molecular mechanisms would help in the development of novel regulating agents for reproductive performance of humans and livestock species.